Aplicación de una guía de métodos y estrategias para desarrollar el pensamiento crítico dirigido a estudiantes de décimos de ee.gg.bb. en el área de lengua y literatura del colegio nacional “José Peralta” del cantón Salcedo la parroquia Mulalillo en el año lectivo 2012- 2013 - Guashpa Coque, Carlos Humberto (2015)
This researching has as main objective to develop a paper for the school applying manual methods and strategies to develop critical thinking same way towards teachers and students, so you can share your pare knowledge it will be based on the fundamental importance in the society, as well as knowing that cause permanent damage to the students, trying to achieve with this work the students improve methods and strategies to go one way to strengthen education. This research in was conducted at the National "Jose Peralta" High School Mulalillo Parish, it had the collaboration of the director and students, which allowed for a better look at a manual method and strategies. Descriptive researching was used for the application of work, using interviewing techniques, survey and observation….